Quantitative Evaluation of the Adaptation Flexibility in Intelligent Architecture Systems - Al-Janabi, Israa Mohsin Kadhim; Al- Khafaji, Rashaa Malik Musa (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Adaptation is a normative practice in the human world, but adaptation is often forced due to undesirable external change, as systems (functional, structural and aesthetic) play an essential role in the adaptation of the building through adoption of intelligent design and use of technology with the aim of improving building and making it a part of its urban environment (Social, economic, physical ... etc.). The research problem lies in the fact that most modern buildings are separated from their surroundings, which led to the emergence of unique and distinct structures from the context, and systems intelligence became represented in smart technologies and systems, as buildings and user behaviors became subject to the control of the machine, and at the same time the continued existence of traditional buildings. With integrated intelligent design systems, and in depended on that problem, the research hypothesis was determined, which was (the building’s adaptation is related to the degree of flexibility available in the architectural system and the integration of architectural systems together according to the passive and the active strategy for both micro and macro levels). The research aims to provide an integrated measurement approach that combines the quantitative approach that depends on mathematical equations and formulas, and qualitative (analytical) approach represented in an integrated theoretical and practical framework that measures the indicator of flexibility of adapting intelligent systems in a group of selected samples. Through this, it was concluded that the buildings are adaptive when they combine design and technical intelligence and rely on both passive and active strategies in a balanced method and according to the influence, the nature of the system and the integration of systems, or at least the integration of two systems.